The flim-flam fairies - Katz, Alan.; Slack, Michael H., 1969- (Philadelphia, PA : Running Press Kids, 2008)
A variety of fairies, including the Snot Fairy, the Dirty Underwear Fairy, and the Earwax Fairy, encourage children to leave things under their pillow that shouldn't be there in an attempt to take over the Tooth Fairy's job.
3.0
K-3
Keywords: Fairies -- Juvenile fiction; Fairies -- Fiction; Humorous stories; Fairies -- Fiction; Humorous fiction